Pasture related characteristics and management strategies associated with udder health in farms with an automatic milking system : impact on somatic cell count and milking frequency - Laufors, Emma (SLU/Dept. of Clinical Sciences (until 231231), 2022)
Udder health plays a central role in the dairy industry and poor udder health can entail both negative economic and animal welfare consequences as well as increased antimicrobial use. The somatic cell count (SCC, a commonly used measurement of udder health) has been observed to increase during the summer season both in Sweden and in other countries. One contributing factor to this is believed to be heat stress which, among other things, influences the immune function of dairy cattle and other animals. With increasing temperatures and a higher vulnerability in high producing dairy cows there is a need to try to prevent the heat stress during warmer periods and to keep up a good udder health. The aim of the present study was to investigate the impact of warmer periods on SCC and milking frequency on farms with an automatic milking system (AMS) as well as explore the different pasture characteristics and management strategies used on these farms. In addition, the effect of these strategies in maintaining the SCC during warmer periods and grazing season is investigated. The study is based on 26 phone interviews with farmers that has an automatic milking system (AMS). The interview included questions about their pasture, feed, udder health, milking system focusing on their experiences during the summer months. The selection of farms for the interviews were based on data from 2017 to 2019 from the Swedish cattle database (SCD) and included farms that have an increase in SCC in the summer and those that are less affected. The answers were categorized into different groups and mainly analysed considering the mean proportional difference in SCC between winter and summer from 2017-2019, mean summer SCC 2017-2019 and milking interval 2021. They were analysed using the statistical tests Mann Whitney test and Kruskal-Wallis. A significant seasonal difference between winter and summer was found regarding both SCC and milking frequency, while the SCC increased the milking interval decreased during the summer. Limiting water to only the barn was not beneficial to maintain the same milking interval during summer. The udder health on farms where cows had a low intake of roughage on pasture and no access to shade on pasture was less impacted by the summer season, possibly due to these cows spending more time inside the barn. Similarly, cows with limited access to pasture appeared to have a higher milking interval compared to those with unlimited access to pasture. It is hard to draw any conclusions from this study, other than on the included farms the SCC increased, and the milking frequency decreased during the summer compared to the winter. By studying the SCC and milking frequency of the participating farms some were successful in maintaining them during summer. Which shows that it is possible to maintain the udder health during the summer combined with an AMS and grazing. Further research is needed looking at characteristics and management strategies both inside the barn and on pasture to completely understand why there is a seasonal pattern with a higher SCC during summer.